Migration area of the Tsushima Warm Current Branches within the Sea of Japan: Implications from transport of 228Ra. (1st July 2017) - Inoue, M.; Shirotani, Y.; Furusawa, Y.; Fujimoto, K.; Kofuji, H.; Yoshida, K.; Nagao, S.; Yamamoto, M.; Hamajima, Y.; Honda, N.; Morimoto, A.; Takikawa, T.; et al.
Abstract: We investigated lateral profiles of 228 Ra (half-life; 5.75 years) activity and 228 Ra/ 226 Ra (1600 years) activity ratio using 241 surface water samples collected in/around the Sea of Japan and the East China Sea (ECS) during June–October of 2009–2014. In the ECS, the 228 Ra/ 226 Ra ratio in the surface waters exhibited markedly wide variation (<0.05–3.5) in June, predominantly reflecting the mixing between the 228 Ra-rich continental shelf water and the 228 Ra-depleted Kuroshio Current water. In July, the surface waters of the central Sea of Japan (135–138°E) became separated into three currents: the Offshore Branch of the Tsushima Warm Current (OBTWC) ( 228 Ra/ 226 Ra =0.7–1.2) at 39–41°N, the Coastal Branch of the TWC (CBTWC) (~0.7) on the southern side, and sub-Arctic Current (~0.7) on the northern side. From the central to northeastern Sea of Japan, the 228 Ra/ 226 Ra ratio at the surface (0.8–1.0) was within a range between that of the CBTWC and OBTWC. The fraction of continental shelf water in the CBTWC, OBTWC, and in their combined current was estimated to be 11–16%, ~8%, and 10–11%, respectively. Highlights: Surface distribution of 228 Ra in Sea of Japan in June–October was examined. Surface 228 Ra activity ( 228 Ra/ 226 Ra ratio) ranged from 0.8 to 4.3 mBq/L (0.5–2.3). Lateral 228 Ra profile clarified migration area of the Tsushima Warm Current. Fraction of continental shelf water showing lower values in June–July was 8–25%.